The role of cardiac rehabilitation in aviation medicine - Jeffrey Dwyer (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2020)
After a cardiovascular illness, an aviation license becomes invalid until the pilot obtains a special issuance medical certificate from the US Federal Aviation Agency (FAA) affirming successful medical treatment and rehabilitation. Many pilots attempt to regain health and fitness without the benefit of guidance from cardiac rehabilitation practitioners and, therefore, fail to satisfy FAA requirements. I the US, in 2016, more than 10,000 pilots with cardiovascular disorders were denied special issuance of a medical certificate. For many of these pilots with heart disease, participation in a cardiac rehabilitation program may have proven essential for successful completion of a rigorous medical examination that satisfied FAA requirements. This article highlights specific assistance provided by a cardiac rehabilitation program developed for pilots. Program objectives are; 1). the highest possible outcome, 2). establish a safe and effective independent exercise program, 3). obtain measures of compliance and success with an independent exercise program, 4). document tolerance of medications and ensure that the medication regimen complies with FAA guidelines, 5). document stability of the serum glucose in diabetic patients engaged in rigorous, prolonged exercise, and 6). prepare the patient for performance of a diagnostic treadmill test in which 100% HRmax must be achieved. It is estimated that fewer than 15% of pilots with heart disease utilize services offered by cardiac rehabilitation practitioners.After a cardiovascular illness, an aviation license becomes invalid until the pilot obtains a special issuance medical certificate from the US Federal Aviation Agency (FAA) affirming successful medical treatment and rehabilitation. Many pilots attempt to regain health and fitness without the benefit of guidance from cardiac rehabilitation practitioners and, therefore, fail to satisfy FAA requirements. I the US, in 2016, more than 10,000 pilots with cardiovascular disorders were denied special issuance of a medical certificate. For many of these pilots with heart disease, participation in a cardiac rehabilitation program may have proven essential for successful completion of a rigorous medical examination that satisfied FAA requirements. This article highlights specific assistance provided by a cardiac rehabilitation program developed for pilots. Program objectives are; 1). the highest possible outcome, 2). establish a safe and effective independent exercise program, 3). obtain measures of compliance and success with an independent exercise program, 4). document tolerance of medications and ensure that the medication regimen complies with FAA guidelines, 5). document stability of the serum glucose in diabetic patients engaged in rigorous, prolonged exercise, and 6). prepare the patient for performance of a diagnostic treadmill test in which 100% HRmax must be achieved. It is estimated that fewer than 15% of pilots with heart disease utilize services offered by cardiac rehabilitation practitioners.